Canada's emerging foresight landscape: observations and lessons. Issue 5 (6th July 2020) - Wilner, Alex; Roy, Martin
Abstract : Purpose: The purpose of this paper is twofold: to introduce scholars and practitioners of foresight to the emerging Canadian foresight ecosystem, and to provide lessons learned on developing policy foresight from the Government of Canada context. Design/methodology/approach: The paper provides a series of lessons based in part on informal and indirect observations and engagement with established Canadian foresight entities, including Policy Horizons Canada, and numerous newly established foresight initiatives at Global Affairs Canada, Standards Council of Canada and the Canadian Forest Service. Findings: The paper finds that Canada's newly emerging foresight units and initiatives face structural, institutional and organizational challenges to their long-term success, including in concretely measuring foresight outcome (rather than simply output) in policy making. Originality/value: The paper provides a unique and empirically driven perspective of the foresight ecosystem that has emerged within the Canadian federal public service since 2015. Lessons are culled from this emerging network of Canadian foresight practitioners for international application.